Modelo econométrico de gestión exitosa para la empresa familiar colombiana (2023)
Given the great importance and impact of family companies in the current global economic context, it is pertinent to make focused efforts to contribute to their development, strengthening, competitiveness, and sustainability over time, especially with regard of their administrative weaknesses, despite representing 80% of the organizations, 70% of employment generation, and more than 50% of GDP in most countries around the world. In this sense, this article presents an econometric management model based on the most representative variables associated with business success in family organizations, aiming to offer a space for analyzing and reflecting on their administrative work, in order to implement corporative strategies that promote the competitiveness of these organizations within the current context of globalized markets. © 2017 Universidad Católica de Colombia.